Blood pressure, heart diseases and lifestyles of elderly - Paula Cristina Araújo Morais; Rafaella Pessoa Moreira; Paula Alves de Lima; Maria das Graças Fernandes Silva; Jerry Deyvid Freires Ferreira; Emilia Soares Chaves Rouberte (Rev Rene)
Objectives: to investigate the blood pressure values; to identify the history of cardiovascular diseases and lifestyles of elderly at a social assistance reference center. Methods: cross-sectional study, conducted with fifty elderly. A form with questions regarding social data, history of diseases and lifestyles was applied. In sequence, the blood pressure was checked. Results: it was observed that 73.3% of the elderly had pressure alterations. Systolic alterations were identified in 73.3%, and diastolic, in 10% of the elderly. The most frequently referred cardiovascular diseases were hypertension (70%), diabetes mellitus(38%) and dyslipidemia (32%). The most common risk factors were current or past use of tobacco whether active (68%) or passive (26%), and physical inactivity (48%). Conclusion: people with altered blood pressure and associated risk factors were identified. This situation may contribute to directing nursing care and addressing the real needs of elderly population.